2016
DOI: 10.1590/1516-3180.2015.01691609
|View full text |Cite
|
Sign up to set email alerts
|

Meat intake among adults: a population-based study in the city of Campinas, Brazil. A cross-sectional study

Abstract: CONTEXT AND OBJECTIVE: Meat is a food with high nutritional density that has significant participation in the Brazilian diet. However, in excess it can cause harm to health. The aim of this study was to analyze the meat intake (g/day) among adults according to sociodemographic, behavioral and health situation characteristics, and to assess the types of meat most consumed. DESIGN AND SETTING: Cross-sectional population-based study conducted in the city of Campinas, São Paulo, Brazil, in 2008 and2009. METHODS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
0
6
0
6
Order By: Relevance
“…Following a diet rigorously is not easy, since patients are forced to veer away from their eating habits. An additional factor is that in Brazil people eat large amounts of protein in the form of beans, beef, milk, and dairy products, 50 , 51 which makes the compliance to a low-protein diet all the more difficult. Data from the Household Budget Survey of 2009 showed that the most popular food items in the nation were beans, rice, meat, fruit juice (industrialized and fresh), carbonated drinks, and coffee.…”
Section: Discussionmentioning
confidence: 99%
“…Following a diet rigorously is not easy, since patients are forced to veer away from their eating habits. An additional factor is that in Brazil people eat large amounts of protein in the form of beans, beef, milk, and dairy products, 50 , 51 which makes the compliance to a low-protein diet all the more difficult. Data from the Household Budget Survey of 2009 showed that the most popular food items in the nation were beans, rice, meat, fruit juice (industrialized and fresh), carbonated drinks, and coffee.…”
Section: Discussionmentioning
confidence: 99%
“…The higher zinc and vitamin B12 intake among obese men might be related to higher protein intake, mainly animal protein intake, since proportion of energy from protein was slightly higher among obese people. Brazilian national data of food intake showed that prevalence of all meat intake (beef, pork meat, chicken, processed meat) were greater among men than women [29][30][31] while men had lower prevalence of vegetables and fruit intake compared to women 12,32 .…”
Section: Discussionmentioning
confidence: 96%
“…Regarding red meat intake, from 2007 to 2014, red meat consumption remained stable in Brazil [19]. The average meat intake among Brazilians from Campinas, São Paulo, in 2008-2009 was 182.3 g. Women and the population older than 49 years showed the lowest intake [20].…”
Section: Discussionmentioning
confidence: 99%